Review of indigenous peoples policy and institutional grounding - Sonny N. Domingo; Arvie Joy A. Manejar (Philippine Institute for Development Studies (PIDS), 2020)
Around 300 million indigenous peoples have been identified across 70 countries, 14 million of them are located in the Philippines with their cultural zones taking up as much as 44 percent of the country's land area. There has been much confusion regarding their identity and rights, resulting to a lengthy policy and institutional evolution which eventually resulted to the passage of the Indigenous Peoples Rights Act in 1997 and the establishment of the National Commission of Indigenous Peoples (NCIP). It took almost a decade for the institution to issue its salient guidelines and regulations like the delineation of ancestral domains, and free, prior and informed consent. This resulted to numerous opportunities foregone in leveraging cultural communities and their ancestral domains against encroachment. The landmark legislation safeguarded essential core rights of the IPs/ICCs. Although seemingly apt protection to IP/ICC rights is accorded by IPRA, the protection of these rights remained contentious on the ground. The IPs/ICCs true empowerment is visible only through their claim and stewardship of ancestral domains, preservation of the integrity of their cultural heritage, and the protection of their basic human rights and social entitlements. Going forward, the IPs/ICCs must assume their rightful place as empowered stewards of their historical domains, and mainstream their interests and advocacies. The Commission, as the enabling institution, would have to review its bureaucratic functions and address the roots of certain weaknesses to better deliver mandated services, and own its critical role in safeguarding the welfare of IPs/ICCs.
Keywords: 330; indigenous peoples; welfare; IPRA; culture